The role of community agreeableness and digital intelligence to improve SME's innovation performance / Dita Prameswari and Olivia Fachrunnisa - Prameswari, Dita; Fachrunnisa, Olivia (2020)
The purpose of this study is to discuss how the role of community, sharing of knowledge between organizations, and digital intelligence on the performance of innovations is conceptualized to develop community capacity. Digital economic distribution can develop many SMEs in several regions in Central Java. As an entrepreneurial trend, innovation has a very important role for SMEs because it must have the ability to use digital technology properly. Efforts to Improve Performance Held by Renewing SMEs for Communities that have the same goal are called Community Agreeableness. Benefits of creating a community are a place to share knowledge and improve knowledge and skills within the SME community supported by digital intelligence. While the method used is a kind of quantitative explanatory research. The sample in this study amounted to 175 SMEs in Central Java who have used digital technology for online marketing and have used at least 1 year. The types of data in this study were obtained from primary data. Primary data were obtained directly from the main sources either from individuals, namely a questionnaire in the form of google which was distributed via WhatsApp personally to each respondent. Data collection methods are used through questionnaires and will then be analyzed with Partial Least Square (PLS) statistical analysis techniques. The results showed that community approval had a positive and significant effect on knowledge sharing between organizations, community approval was positively and significantly related to collaboration skills, knowledge sharing between organizations had a positive and significant effect on innovation performance, collaboration skills had a positive and significant effect on innovation performance, and digital intelligence is able to moderate the relationship between sharing knowledge between organizations and innovation performance. Hence, increasing the capacity of the community plays an important role in improving innovation performance in SMEs.